A New Class of Conjugated Ionic Polyacetylene. Cyclopolymerization of Dihexyldipropargylammonium Salts by Metathesis Catalysts - Kang, K.-L.; Kim, S.-H.; Cho, H.-N.; Choi, K.-Y.; Choi, S.-K. (1993)
A new class of substituted ionic polyacetylene was synthesized by metathesis polymerization with transition-metal catalysts. The monomers used were dihexyldipropargylammonium salts having bromide and tosylate as counteranions. It was found that MoCl5-based catalyst systems were very effective for the cyclopolymerization of the present ionic monomers. The resulting dark-red polymers exhibited good solubility in polar organic solvents such as methanol, DMSO, DMF, THF, CHCl3, etc., indicative of their ionic nature. Structure of the polymers was confirmed by IR, UV-visible, and 1H and 13C NMR spectroscopy. When doped with an acceptor such as iodine, the polymers exhibited a substantial increase in electrical conductivity (10？3 S/cm) compared to the undoped state (10？9 S/cm). ？ 1993, American Chemical Society. All rights reserved.
Keywords: Ammonium compounds; Catalysis; Doping (additives); Electric conductivity; Polymerization; Spectroscopic analysis; Cyclopolymerization; Dihexyldipropargylammonium salts; Metathesis catalysts; Polar organic solvents; Polyacetylenes